Dinamika Kewenangan Lembaga Negara Pasca Amandemen UUD 1945 - Thaher, Irmanjaya (Gapenas Publisher, 2025)
The Indonesian constitutional system underwent a fundamental transformation following the amendments to the 1945 Constitution, particularly in the distribution of authority within state institutions. Studying the dynamics of authority is crucial for understanding the checks and balances mechanism in democratic and constitutional governance.This research analyzes the institutional transformation of the People's Consultative Assembly (MPR), examines the patterns of relationships between state institutions, evaluates the role of the Constitutional Court as an interpreter of the constitution, and analyzes the redistribution of legislative authority through the strengthening of the House of Representatives (DPR) and the establishment of a bicameral system with the Regional Representatives Council (DPD) to foster a democratic legislative process.The research methodology employed a Systematic Literature Review (SLR) conducted in a systematic, planned, and transparent manner to identify, evaluate, and synthesize various relevant scholarly articles to obtain a comprehensive overview of the development of research concepts.The results show that the MPR has transformed from a supreme institution to an equal institution. Relations between state institutions are built on the pillars of constitutional supremacy and the separation of powers. The Constitutional Court serves as a guardian of the constitution, resolving disputes over authority. The establishment of a bicameral system strengthens the checks and balances mechanism in the national legislative process.The conclusion of the study confirms that the amendment to the 1945 Constitution has succeeded in creating a more democratic state architecture with the transformation of the authority of the MPR, strengthening of constitutional supremacy through the Constitutional Court, and redistribution of legislative authority which has resulted in a more accountable, participatory, and representative government system towards national and regional interests within the framework of a democratic state based on the rule of law.